The Influence of the Principal’s Transformational Leadership and Organizational Work Culture on Teachers’ Performance at Public Middle Schools - Ruli Zardi; Syarwani Ahmad; Heri Setyo Nugroho (Journal of Social Work and Science Education, 2026)
This study aims to analyze the influence of principal’s transformational leadership and organizational work culture on teachers’ performance in Public Junior High Schools in Banyuasin III District. Employing a quantitative causal-associative design, the research involved 103 teachers selected through Slovin’s formula and proportional random sampling. Data were collected using Likert-scale questionnaires and analyzed via multiple linear regression. The results reveal that: (1) transformational leadership has a positive and significant partial effect on teachers’ performance; (2) organizational work culture also exerts a positive and significant partial effect; and (3) simultaneously, both variables significantly predict teachers’ performance, with an Adjusted R Square of 0.905, indicating that 90.5% of the variance in performance is explained by the two predictors. The novelty lies in empirically demonstrating the combined dominance of these factors within a specific regional context, where prior studies often examined them separately. Practically, these findings underscore that sustainable teacher professionalism hinges on the synergy between visionary principals and a conducive workplace climate. This study contributes actionable evidence for educational policymakers and school administrators, emphasizing that investment in leadership development and cultural strengthening is not ancillary but essential for optimizing human resource quality in public secondary education.